Twenty-Year Trends in Coronary Risk Factors in North Karelia and in Other Areas of Finland - VARTIAINEN, ERKKI; PUSKA, PEKKA; JOUSILAHTI, PEKKA; KORHONEN, HEIKKI J; TUOMILEHTO, JAAKKO; NISSINEN, AULIKKI (International Journal of Epidemiology, 1994)
Background . The North Karella Project, a major demonstration programme for coronary heart disease (CHD) prevention, began in the eastern provInce of North Karella in Finland in 1972. A number of other national CHD prevention activities have also been undertaken particularly since 1977. In the 1980s, a national strategy was developed for CHD prevention. This paper reports the 20-year changes in risk factors In North Karelia and In the original reference area of the project and the 10-year changes In a thIrd area in southwestern Finland. Methods . The results are based on comparable surveys of cross-sectional population samples, aged 30–59 years, every fifth year since 1972. Results . During the first 5 years total cholesterol and blood pressure fell more in North Karelia than in the reference area, but subsequently changes have been about the same in both areas. The decline levelled oft between the 1982 and 1987 surveys. This resulted In new nationwide preventive activities and during the last 5 years major declines in both serum total cholesterol and blood pressure have been observed. Smoking reduced more during the first 10 years in North Karelia than in Kuoplo province. During the last 10 years a small decline has been observed In both areas. No change In smoking has occurred In southwestern Finland in the last 10 years. Conclusions . A major declIne In cardiovascular disease risk factors has been observed in the last 20 years In Finland. This declIne was associated with the launch of the national demonstration project in North Karelia in the 1970s and with subsequent major national activities thereafter.